Bacteriocin-like peptides encoded by a horizontally acquired island mediate Neisseria gonorrhoeae autolysis. - Katy Poncin; Samantha A McKeand; Hayley Lavender; Kacper Kurzyp; Odile B Harrison; Annabell Roberti; Charlotte Melia; Errin Johnson; Martin C J Maiden; David R Greaves; Rachel Exley; Christoph M Tang (PLoS Biology)
Neisseria gonorrhoeae is a human-specific pathogen that causes the important sexually transmitted infection, gonorrhoea, an inflammatory condition of the genitourinary tract. The bacterium is closely related to the meningococcus, a leading cause of bacterial meningitis. Both these invasive bacterial species undergo autolysis when in the stationary phase of growth. Autolysis is a form of programmed cell death (PCD) which is part of the life cycle of remarkably few bacteria and poses an evolutionary conundrum as altruistic death provides no obvious benefit for single-celled organisms. Here, we searched for genes present in these 2 invasive species but not in other members of the Neisseria genus. We identified a ~3.4 kb horizontally acquired region, we termed the nap island, which is largely restricted to the gonococcus and meningococcus. The nap island in the gonococcus encodes 3 cationic, bacteriocin-like peptides which have no detectable antimicrobial activity. Instead, the gonococcal Neisseria autolysis peptides (Naps) promote autolytic cell death when bacteria enter the stationary phase of growth. Furthermore, strains lacking the Naps exhibit reduced autolysis in assays of PCD. Expression of Naps is likely to be phase variable, explaining how PCD could have arisen in these important human pathogens. NapC also induces lysis of human cells, so the peptides are likely to have multiple roles during colonisation and disease. The acquisition of the nap island contributed to the emergence of PCD in the gonococcus and meningococcus and potentially to the appearance of invasive disease in Neisseria spp.